Efektivitas Robot AI Adaptif dalam Mendukung Pembelajaran Inklusif bagi Mahasiswa dengan Learning Disabilities di Universitas Darwan Ali - Ismail, Andy; Andriyati, Yuli; Minarni, Minarni; Febriani, Nova; Kristin Rahel, Herlina (Journal of Comprehensive Science, 2024)
This study developed an adaptive AI robot as a learning aid for students with learning disabilities (LD) at Universitas Darwan Ali. The robot is equipped with text-to-speech, speech-to-text, voice and facial recognition features, and adaptive algorithms that adjust content delivery to match students' literacy levels. A research and development approach with agile methodology was employed, encompassing needs identification, design, testing, and implementation phases. Results indicate a 30% increase in academic comprehension and an 82% satisfaction rate among students. Additionally, the AI robot serves as a "learning companion" providing social-emotional support, which enhances learning motivation for LD students. Thus, this adaptive AI robot effectively supports inclusive education at Universitas Darwan Ali.